The Marketing Communication Strategy of RSIA Bunda Jakarta Through Instagram Social Media to Enhance Brand Awareness - Kurniasari, Dina Rizky (Riwayat: Educational Journal of History and Humanities, 2024)
The development of the health sector in Indonesia has made significant progress, reflected in the increase in the number of hospitals in Indonesia. As the sector grows, people are increasingly realizing the importance of quality healthcare. This phenomenon is the basis for strategic steps of hospitals, such as RSIA Bunda Jakarta which utilizes Social Media, especially Instagram, as the main means of carrying out marketing activities. This research uses the basis of marketing communication theory, especially in the context of message media strategy. This research adopts qualitative methodology with a descriptive approach. Data are obtained by data collection techniques through observation, interviews and documentation. The results showed that RSIA Bunda Jakarta has set their marketing goals on Instagram as the main means of maintaining existence and increasing brand awareness. The right segmentation of the female and Gen Z audience confirms RSIA Bunda Jakarta's understanding of the preferences and needs of their target market. The messaging strategy is supported by accurate medical information, engaging educational content, and active interaction with the audience thus strengthening credibility. As well as at the media strategy stage, adjusting Instagram content and features to audience needs, choosing the right upload time, and utilizing influencer moments and engagement. Overall, this study concluded that the marketing team of RSIA Bunda Jakarta itself has succeeded in carrying out marketing communication strategies through Instagram to increase brand awareness.